Sesquiterpenoids from The Stem Bark of Aglaia cucullata (Meliaceae) and Their Cytotoxic Activity Against A549 Lung Cancer Cell Lines - Mustaqim, Iqbal Wahyu; Harneti, Desi; Naini, Al Arofatus; Hilmayanti, Erina; Darwati, Darwati; Nurlelasari, Nurlelasari; Mayanti, Tri; Maharani, Rani; Farabi, Kindi; Hidayat, Ace Tatang; Supratman, Unang; Fajriah, Sofa; Azmi, Mohamad Nurul; Shiono, Yoshihito (Universitas Jenderal Soedirman, 2024)
ABSTRACT. Sesquiterpenoids are a class of terpenoid compounds with a remarkable diversity of structures and biological activities. Sesquiterpenoids are primarily found in higher plants, such as the Meliaceae family's Aglaia genus. Aglaia cucullata is a species of Aglaia that is still rarely explored and can potentially contain sesquiterpenoid compounds with cytotoxic activity. Hence, the research intended to isolate sesquiterpenoids from the n-hexane extract of A. cucullata stem bark and evaluate their cytotoxic effect against A549 lung cancer cells. Compounds 1 and 2 were isolated and purified from n-hexane extracts utilizing various chromatographic techniques. The structure of compounds 1 and 2 was determined by analyzing various spectroscopic methods (IR, MS, and NMR) and comparing them to previously reported spectral data. Compound 1 was identified as an isodaucane-type sesquiterpenoid, 10-hydroxy-6,10-epoxy-7(14)-isodaucane, and was first reported in Meliaceae family. Compound 2 was confirmed as an eudesmane-type sesquiterpenoid, eudesm-4(15)-ene-1β,6α-dihydroxy, and was first reported in Aglaia cucullata. Cytotoxic activity of 1 and 2 were investigated in vitro against A549 lung cancer cells using the PrestoBlue assay and resulted in inactive and low cytotoxicity with IC50 values of 292.77 and 90.55 μM, respectively. Key words: Aglaia cucullata, , A549 cell lines, cytotoxic activity, Meliaceae, sesquiterpenoids.